Nesidiocoris tenuis as a pest in Northwest Europe: Intervention threshold and influence of Pepino mosaic virus. (6th July 2020) - Moerkens, Rob; Pekas, Apostolos; Bellinkx, Stijn; Hanssen, Inge; Huysmans, Marlies; Bosmans, Lien; Wäckers, Felix
Abstract: The use of Nesidiocoris tenuis (Hemiptera: Miridae) as a biocontrol agent is controversial as it is considered a pest in Northwest European tomato greenhouses, due to its tendency to damage the plant and fruit. Necessary chemical plant protection products to control N . tenuis have toxic side effects on important beneficials like Macrolophus pygmaeus (Hemiptera: Miridae), which jeopardizes the whole IPM programme. In this study, several commercial tomato greenhouses were monitored for mirid populations. The relationship between the number of N. tenuis individuals and plant damage was assessed in function of availability of prey and interaction with M. pygmaeus . These greenhouse data were used to determine a practical density intervention threshold. Next, the hypothesis that a Pepino mosaic virus (PepMV) infection increases plant and fruit damage by N. tenuis (as has been shown for M. pygmaeus ) was tested. Plant damage occurred when the average number of predatory bugs in the head of the plant exceeded 16 per ten plants. Plant damage increased in severity at increasing predatory bug densities, independent of the availability of prey and M. pygmaeus presence. Plant and fruit damage were not affected by the presence of PepMV, as was shown for fruit damage in previous studies for M. pygmaeus . Our study provides a practical density intervention threshold for growers in greenhouse crops. Simple monitoring of the number of predatory bugs in the head of the plant can be used to take specific biocontrol actions. It was also shown that only the predatory bug N. tenuis itself causes damage, and there is no interaction with PepMV.